Implementasi Metode Lalaran dalam Meningkatkan Daya Ingat dan Pemahaman Ilmu Nahwu pada Kitab As Sabrowi Santri Putri di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan: Penelitian - Uswatun Hasanah; Mustaqim Hasan; Hendika Adi Nugraha (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study was to determine how the implementation of the lalaran method is carried out, the extent to which it is effective in improving students' memory and understanding, and the supporting and inhibiting factors. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study were middle-class female students who had studied the As-Sabrowi Book. The results of the study showed that the application of the lalaran method was able to improve students' memory of the rules of nahwu, facilitate reading, and facilitate understanding of the meaning of sentences. In addition, this method also forms an attitude of discipline, perseverance, and enthusiasm for learning in students. The supporting factors for the implementation of this method are student discipline and support from teachers, while the inhibiting factors are boredom and time constraints. Overall, the lalaran method has proven effective in improving memory and understanding of nahwu science at the Hidayatul Mubtadiin Islamic Boarding School.